Mechanochemical Approaches to Pharmaceutical Cocrystal Formation and Stability Analysis - Lin, Shan-Yang (Current Pharmaceutical Design, 2016)
Solid-state mechanochemical grinding is important for promoting cocrystal formation, particularly in the design of new solids in the pharmaceutical industry. Pharmaceutical cocrystals are defined as crystalline materials comprising an active pharmaceutical ingredient (API) and one or more appropriate coformers in a definite stoichiometric ratio, formed via non-covalent interactions. Recently, both the US FDA (2013) and the EU EMA (2015) provided a Guidance for Industry and a Reflection Paper, respectively, emphasizing that cocrystals are a new type of substance with potential applications in the pharmaceutical industry. This paper contains a brief and systematic overview of pharmaceutical cocrystals prepared by four grinding processes: neat grinding, solvent-assisted grinding, thermal stress after neat grinding, and polymer-assisted grinding. The paper also highlights some examples of pharmaceutical cocrystals prepared by the above grinding approaches, and discusses the stability of cocrystals prepared by mechanical grinding. Also, an overview of cocrystals that are commercially available or undergoing clinical trials is given. A novel methodology for real-time and in situ monitoring of mechanochemical grinding reactions using various analytical techniques is addressed and can be expected to be applied in the near future.
Keywords: Pharmaceutical cocrystal